1991
DOI: 10.1177/1077727x9102000103
|View full text |Cite
|
Sign up to set email alerts
|

User Input in Housing Design: The Interdisciplinary Challenge

Abstract: A consortium composed of home economists, architects, engineers, and horticulturists at the University of Nebraska-Lincoln undertook a project to develop housing designs that would respond to the current and future needs and desires of people living in Nebraska. The consortium hoped to reduce the considerable gap between the thinking of designers and that of the people for whom they design (users) by linking designers with professionals in social sciences. This article contains a discussion of the user evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…As a matter of fact living in a non-energy efficient house implies not having good financial conditions (Burholt & Windle, 2006) and old people represent a high percentage of this part of the society (Sefton, 2005). The necessity to have a heated house is an important matter among old people because they spend there more time during winter, hence the functioning hours of the heating system (cost) are higher than other ranges of age (Baltes, Mayr, Borchelt, Maas, & Wilms, 1993;Baltes, Maas, & Wilms, 1999;Gabb, Lodl, & Combs, 1991;Healy & Clinch, 2002). All those factors require certain regulations providing help to old people who are not in a good position financially and socially speaking (Chard & Walker, 2016).…”
Section: Energy Implications and Social Costsmentioning
confidence: 99%
“…As a matter of fact living in a non-energy efficient house implies not having good financial conditions (Burholt & Windle, 2006) and old people represent a high percentage of this part of the society (Sefton, 2005). The necessity to have a heated house is an important matter among old people because they spend there more time during winter, hence the functioning hours of the heating system (cost) are higher than other ranges of age (Baltes, Mayr, Borchelt, Maas, & Wilms, 1993;Baltes, Maas, & Wilms, 1999;Gabb, Lodl, & Combs, 1991;Healy & Clinch, 2002). All those factors require certain regulations providing help to old people who are not in a good position financially and socially speaking (Chard & Walker, 2016).…”
Section: Energy Implications and Social Costsmentioning
confidence: 99%
“…Special programmes that target remodelers already are being offered by groups such as the National Association of Home Builders with their Certified Aging in Place certificate that focuses on universal design and the specifics of marketing to and serving older clients, and emphasizes good business practices (http://www.nahb.org/caps). Gabb et al (1991) found that consumers had trouble visualizing and evaluating house plans. New three-dimensional computer technologies will enable consumers to better visualize universal design features in their current home or in their selected house plan by bringing them to life on the screen.…”
Section: Implications For Marketing Universal Designmentioning
confidence: 99%